- #1

phrankle

- 6

- 0

This probably has a really simple answer.

Forr u=x^2-y^2 and v=x^2+y^2

x and y are apparently the dependent variables. But the independent variable is the input while the dependent variable is the output, so since u=f1(x,y) and v=f2(x,y) shouldn't they (u and v) be the dependent variables?

Forr u=x^2-y^2 and v=x^2+y^2

x and y are apparently the dependent variables. But the independent variable is the input while the dependent variable is the output, so since u=f1(x,y) and v=f2(x,y) shouldn't they (u and v) be the dependent variables?

Last edited: